Perilaku Masyarakat Dalam Membuang Air Besar Desa Rindu Hati - Nia Kontesa; Aplina Kartika Sari; Haidina Ali (Direktorat Politeknik Kesehatan Makassar, 2024)
There are still places in Indonesia where careless defecation occurs. The severity of the disease increases with the proportion of indiscriminate bowel movements. According to Riskesdas 2018 statistics, Central Bengkulu Regency has 17,159 (63%) healthy toilets. This means that 37% of people have not complied with it. Finding out how people defecate in Rindu Hati village, Central Bengkulu Regency, is the goal of this study. A quantitative descriptive study approach that explains the knowledge, attitudes, and behaviors of the defecating community in Rindu Hati Village, Central Bengkulu Regency. The 72 participants in the sample represent the population of Rindu Hati Village, which is the research population. The sampling strategy uses descriptive data analysis and random sampling techniques. According to the study's findings, of the 72 knowledgeable respondents, more than half 39% of rural communities, 25% of educated people, and 36% of low-knowledge populations are in dire need of sufficient information. regarding feces. The majority of respondents, or as many as 62.5%, had a smaller influence on bowel movements, while almost half, or as many as 44.4%, had a negative attitude towards bowel movements. Of the respondents, more than half (55.6%) have a positive attitude towards bowel movements. According to this survey almost half of the residents living in Rindu Hati Village, Central Bengkulu Regency, have enough knowledge, almost half have a bad attitude, and more than half have little defecation. By taking part in activities organized by health professionals, adopting a clean and healthy lifestyle, establishing attitudes about bowel movements, and encouraging good practices to keep homes and environments clean and healthy at all times, the public is expected to gain more information.. Keywords : knowledge; attitudes; actions; defecation.